ANALISIS DATA KUANTITATIF “EFEKITIVITAS METODE GRAPHOMOTOR TERHADAP KEMAMPUAN MENULIS PESERTA DIDIK” - Muh Zulkifli (Al-mujahidah, 2020)
Seeing the results of observations, it was found various problems, namely: the students' low writing ability, the lack of training in the hand muscles so that students quickly felt tired during writing activity. The purpose of this study was to analyze quantitative data to determine the effectiveness of the graphomotor method on students' writing skills. This type of research is experimental quantitative research, with a Pre Experimental Design used. The results of pre-test post-test data analysis using the t-test statistical formula showed that the graphomotor method was effective in improving students' writing skills. This is proved after being analyzed using the t-test statistical formula, the value of t_count> t_table is 21.56> 2.12 with db = 17 at a significant level of 5%.